Environmental risk assessment in radioactively contaminated regions - Голяткіна, Т.М.; Тихенко, О.М.; Криворотько, В.М. (Proceedings of National Aviation University (archive), 2006)
Problems related to estimation of ecology safety of the territory which is polluted by radionuclide are concerned. Method of the box models for modeling was proposed. The result of mathematical calculations were applied, and corresponding conclusions were made.